The phenomenon of interaction as a reflection of social processes: ontological approach - Харченко, Ю. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article is carried out conceptualizing interaction phenomenon as social process based on basic ontological approaches.